The role of prenatal substance exposure and early adversity on parasympathetic functioning from 3 to 6 years of age. (3rd September 2013) - Conradt, Elisabeth; Abar, Beau; Sheinkopf, Stephen; Lester, Barry; Lagasse, Linda; Seifer, Ronald; Shankaran, Seetha; Bada‐Ellzey, Henrietta; Bauer, Charles; Whitaker, Toni; Hinckley, Matt; Hammond, Jane; et al.
ABSTRACT We employed latent growth curve analysis to examine trajectories of respiratory sinus arrhythmia (RSA) from 3 to 6 years among children with varying levels of prenatal substance exposure and early adversity. Data were drawn from a prospective longitudinal study of prenatal substance exposure that included 1, 121 participants. Baseline RSA and RSA reactivity to an attention‐demanding task were assessed at 3, 4, 5, and 6 years. Overall, there were significant individual differences in the trajectories of RSA reactivity, but not baseline RSA, across development. Greater levels of prenatal substance exposure, and less exposure to early adversity, were associated with increased RSA reactivity at 3 years, but by 6 years, both were associated with greater RSA reactivity. Prenatal substance exposure had an indirect influence through early adversity on growth in RSA reactivity. Results are in support of and contribute to the framework of allostatic load. © 2013 Wiley Periodicals, Inc. Dev Psychobiol 9999: 1–15, 2013.